ORDE BARU SEBAGAI LANDASAN FABULA DALAM NOVEL ENTROK KARYA OKKY MADASARI: KAJIAN FORMALISME RUSIA - Rokhmansyah, Alfian (Fakultas Ilmu Budaya, Universitas Mulawarman, 2015)
This study focused on the analysis of the facts used to form the fabula which was defamiliarized into sjuzet in the novel Entrok by Okky Madasari. To analyze the facts, Russian Formalism theory and objective approach were used in this study. The results showed that the story in the novel used historical facts from the new order to form fabula. Subsequently the fabula was defamiliarized into sjuzet.The results also indicated that there was a fictionalization process conducted by the author in creating the story which used historical facts.Keywords: fabula, the new order, russian formalism